Gene expression and cellular changes in injured myocardium of Ciona intestinalis - Stokes, Serenity; Palmer, Pooja Pardhanani; Barth, Jeremy L.; Price, Robert L.; Parker, Bella G.; Evans Anderson, Heather J. (Frontiers in Cell and Developmental Biology, 2024)
Ciona intestinalis is an invertebrate animal model system that is well characterized and has many advantages for the study of cardiovascular biology. The regulatory mechanisms of cardiac myocyte proliferation in Ciona are intriguing since regeneration of functional tissue has been demonstrated in other organs of Ciona in response to injury. To identify genes that are differentially expressed in response to Ciona cardiac injury, microarray analysis was conducted on RNA from adult Ciona hearts with normal or damaged myocardium. After a 24- or 48-hour recovery period, total RNA was isolated from damaged and control hearts. Initial results indicate significant changes in gene expression in hearts damaged by ligation in comparison to control hearts. Ligation injury shows differential expression of 223 genes as compared to control with limited false discovery (5.8%). Among these 223 genes, 117 have known human orthologs of which 68 were up-regulated and 49 were down-regulated. Notably, Fgf9/16/20, insulin-like growth factor binding protein and Ras-related protein Rab11b were significantly upregulated in injured hearts, whereas expression of a junctophilin ortholog was decreased. Histological analyses of injured myocardium were conducted in parallel to the microarray study which revealed thickened myocardium in injured hearts. Taken together, these studies will connect differences in gene expression to cellular changes in the myocardium of Ciona, which will help to promote further investigations into the regulatory mechanisms of cardiac myocyte proliferation across chordates.